Shock and damage models in reliability theory - Nakagawa Toshio (London Springer-Verlag, 2007)
This book describe the reliability properties and maintenance policies associated with shock and damage models. It introduces stochastic processes before surveying current developments in shock and damage models. The reliability quantities of each model a
Keywords: Matematical models; Reliability(Engineering)